Long-Term Effects of Elevated Intra-Abdominal Pressure on Testes An Experimental Model of Laparoscopy - Imamoglu, Mustafa; Sapan, Levent; Tekelioglu, Yavuz; Sarihan, Haluk (Urology Journal, 2013)
Purpose: To determine the long-term outcomes of pneumoperitoneum on the testes in an experimental laparoscopy model. Materials and Methods: Twenty-four rats were divided into three groups: Group A, the control group; Group B, exposed to a 10 mmHg intra-abdominal pressure (IAP); and Group C, exposed to a 20 mmHg IAP with CO2 pneumoperitoneum for 60 minutes. After 6 weeks, the testes were removed, and testicular injury score and Johnson score were examined histologically. Germ cell apoptosis was also detected using flow cytometry. Results: A significant difference was determined between all groups in terms of testicular injury scores, Johnson scores, and germ cell apoptosis percentages. For the testicular injury score, there were significant differences between the groups for the right testis (group A versus B, P = .009; group A versus C, P < .0001; and group B versus C, P = .001) and for the left testis (group A versus B, P = .001; group A versus C, P < .0001; and group B versus C, P = .002). Significant differences were determined in the Johnson scores for the right testis between all groups (group A versus B, P = .001; group A versus C, P < .0001; and group B versus C, P = .008, respectively). Percentage of apoptotic testis cells were significantly differed between all groups (P = .001 for each). Conclusion: This study shows that increased IAP during pneumoperitoneum causes histopathology and apoptotically-evident damage to the testes in the long-term, depending on the magnitude of IAP increase, which may cause sub/infertility. Considering the experimental nature of this study, further clinical studies are needed for a more decisive conclusion.